Nanocomposite-coated porous templates for engineered bone scaffolds: a parametric study of layer-by-layer assembly conditions. (20th September 2019) - Ziminska, Monika; Chalanqui, Marine J; Chambers, Philip; Acheson, Jonathan G; McCarthy, Helen O; Dunne, Nicholas J; Hamilton, Andrew R
Abstract: Using the layer-by-layer (LbL) assembly technique to deposit mechanically reinforcing coatings onto porous templates is a route for fabricating engineered bone scaffold materials with a combination of high porosity, strength, and stiffness. LbL assembly involves the sequential deposition of nano- to micro-scale multilayer coatings from aqueous solutions. Here, a design of experiments (DOE) approach was used to evaluate LbL assembly of polyethyleneimine (PEI), polyacrylic acid (PAA), and nanoclay coatings onto open-cell polyurethane foam templates. The thickness of the coatings, and the porosity, elastic modulus and collapse stress of coated foam templates were most strongly affected by the pH of PAA solutions, salt concentration, and interactions between these factors. The mechanical properties of coated foams correlated with the thickness of the coatings, but were also ascribed to changes in the coating properties due to the different assembly conditions. A DOE optimization aimed to balance the trade-off between higher mechanical properties but lower porosity of foam templates with increasing coating thickness. Micromechanical modeling predicted that deposition of 116 QLs would achieve mechanical properties of cancellous bone (>0.05 GPa stiffness and >2 MPa strength) at a suitable porosity of >70%. When capped with a final layer of PAA and cross-linked via thermal treatment, the PEI/PAA/PEI/nanoclay coatings exhibited good indirect cytotoxicity with mesenchymal stem cells. The ability of LbL assembly to deposit a wide range of functional constituents within multilayer-structured coatings makes the general strategy of templated LbL assembly a powerful route for fabricating engineered tissue scaffolds that can be applied onto various porous template materials to achieve a wide range of properties, pore structures, and multifunctionality.